Correlation of starting order to final time for bobsled competition at the 2022 Olympic Games - Hoskins, A. B. (Sports Engineering, 2024)
In the sport of bobsledding, only one bobsled is on the track at any given time, and the start order for heats two, three, and four is based on the current standings of the competition. However, for the first heat, the highly ranked competitors can select their starting position from available slots. Making the right decision on the starting order can influence the competition`s final results. The analysis presented in this manuscript provides scientific backing to the choices being made. This manuscript`s primary focus is analyzing the start order`s impact on the final times for the heats. Olympic bobsledding has four different events: the one-woman, the two-woman, the two-man, and the four-man competitions. These four events are distinctly different, and each event must be analyzed separately from the others. The results show that start order significantly impacts the events` results, but that while there is an overall impact, there are nuances to the impact for the top teams.